FACTORS CONTRIBUTING TO STUDENTS DIFFICULTIES IN ACADEMIC WRITING CLASS: STUDENTS PERCEPTIONS - Algrenita Silvina Budjalemba; Listyani Listyani (UC Journal: ELT, Linguistics and Literature Journal, 2020)
Writing is one of the most difficult skills in learning English as a Second Language (ESL) or English Foreign Language (EFL). Many language learners encountered difficulties from the writing process. At the tertiary level, students are required to produce academic essays, which are difficult and may frustrate students. The purpose of this study was to analyze factors contributing to students difficulties in an Academic Writing course based on the students perceptions. This study used a qualitative method. The instruments used were open-ended questionnaires and interview protocol. In this study, all the participants answers were coded and analyzed descriptively. The participants were 22 students who were taking Academic Writing class for repeaters in Semester I, 2018/2019 academic year, in an English Language Education Program, in a university in Central Java, Indonesia. Questionnaire data were coded and classified by the researcher. In conducting the interview, data were audio-recorded and transcribed. Those data were analyzed to answer the research questions in this study. Based on the findings, there were two factors that caused students difficulties in writing academically. The two factors were internal and external. Internal factors consisted of self-motivation, self-confidence, lack of knowledge and feeling of under pressure. External factors consisted of the teachers teaching style, classroom atmosphere, materials, and writing aspects. This research hopefully can help teachers and instructors in developing appropriate teaching techniques in Academic Writing and minimize students' difficulties in Academic Writing.